Explaining the multiple energy thresholds for damage mechanisms activation in laminate composites under cyclic loadings - Ferreira Motta, Roberto [UNESP]; Alderliesten, René; Zarouchas, Dimitrios; Yutaka Shiino, Marcos [UNESP]; Odila Hilario Cioffi, Maria [UNESP]; Jacobus Cornelis Voorwald, Herman [UNESP] (Elsevier, 2023)
After half a century of developing fatigue delamination prediction models, where accuracy seems more important than physical understanding, this research aims to merge both aspects. To that aim, strain energy release (SER) within the fatigue load cycle was studied using acoustic emission. The correlation between the measured strain energy release and the acoustic emission energy was formulated through a conversion factor to convert one into the other. The strain energy release distribution within the loading cycle indicated that different damage mechanisms are activated in different increments of the load cycle associated with different energy thresholds. The presence of multiple energy thresholds indicated that the application of different loading cycles results in distinct resistances to damage propagation (dU/dA) depending on which energy threshold is crossed.
Keywords: Fractography; Fracture mechanics; Laminates; Stress ratio